Baby bears and how they grow - Buxton, Jane Heath, 1948- ([Washington, D.C.] : National Geographic Society, 1986)
Text and photographs present several kinds of bears, including polar, grizzly, and black, engaged in a variety of activities.
Bibliography: p. [34]
Keywords: Bear cubs -- Juvenile literature; Bears -- Juvenile literature; Mammals -- Infancy -- Juvenile literature